2009
DOI: 10.3354/dao02028
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the amphibian chytrid fungus Batrachochytrium dendrobatidis by Archey’s frog Leiopelma archeyi

Abstract: Archey's frog Leiopelma archeyi is a critically endangered New Zealand endemic species. The discovery of the emerging infectious disease, chytridiomycosis, in wild populations of this frog raised concern that this disease may drive the species to extinction. Twelve wild-caught Archey's frogs naturally infected with the amphibian chytrid fungus Batrachochytrium dendrobatidis were monitored in captivity by observing clinical signs, measuring weight gain, and performing repeated PCR tests. Eight frogs were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…It has been speculated that chloramphenicol therapy causes apoptosis in the skin, killing intracellular sporangia, although the exact mechanism of action is unknown. Although no clinical trial has been conducted, and therefore dose and treatment time have not been assessed, current treatment protocols typically require submersion for two to four weeks 10,11 , making this treatment impractical for terrestrial amphibians. Chloramphenicol has also been restricted in some countries for veterinary use because human exposure has been associated with a rare form of aplastic anemia 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that chloramphenicol therapy causes apoptosis in the skin, killing intracellular sporangia, although the exact mechanism of action is unknown. Although no clinical trial has been conducted, and therefore dose and treatment time have not been assessed, current treatment protocols typically require submersion for two to four weeks 10,11 , making this treatment impractical for terrestrial amphibians. Chloramphenicol has also been restricted in some countries for veterinary use because human exposure has been associated with a rare form of aplastic anemia 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of Bd eradication initiatives have been proposed (Parker et al 2002, Woodhams et al 2003, Forzán et al 2008, Bishop et al 2009, Garner et al 2009, Berger et al 2010, Martel et al 2011. One method exploits the low heat resistance of Bd (Woodhams et al 2003), whereas others using formalin and malachite green have also been reported (Hohreiter & Rigg 2001, Parker et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…A. japonicus is also listed as a CITES Appendix I species (Kaneko & Matsui 2004). The present study aimed to establish a safe and effective method for eradicating Bd in the Japanese giant salamander.Although a number of methods for eradicating Bd have been reported to date (Parker et al 2002, Woodhams et al 2003, Forzán et al 2008, Bishop et al 2009, Garner et al 2009, Nichols & Lamirande 2009, Berger et al 2010, Martel et al 2011, most of these reports have focused on anuran taxa. However, several groups have recently reported methods for treating chytridiomycosis in urodeles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when retested at the research facility, all except one frog had self cured. The last frog also became negative after a short course of topical chloramphenicol (Bishop et al 2009). In addition to this unexpected self cure in captive frogs held at conditions ideal for Bd, the prevalence of Bd in the Whareorino population increased over the next 3 yr, but the abundance of frogs did not appear to decline (Shaw et al 2008a).…”
Section: Introductionmentioning
confidence: 99%